Neurocognitive models of autism - Hooper, Stephen (Henry Stewart Talks, 2011)
What is a theory?, Theoretical notions and autism, Cognitive and developmental perspectives, challenges, Theory of Mind, The Sally-Ann task, Higher order theory of mind tasks, Measurement strategies, Several core deficits, Executive Dysfunction Theory, Key brain regions, From a behavioral perspective, Problems, Studies and findings, Executive dysfunction theory, Central Coherence Theory, Verbal / Non verbal examples, Weak central coherence in Autism, Different levels of complexity, Frith and Happe, From a developmental perspective, Types of assessments and interventions, The search for final common pathway(s), Combining elements of all three theories